Biobanking and cryopreservation of human lung explants for omic analysis. Issue 1 (23rd January 2020) - Chu, Sarah G.; Poli De Frias, Sergio; Sakairi, Yuichi; Kelly, Rachel S.; Chase, Robert; Konishi, Kazuhisa; Blau, Ashley; Tsai, Ellen; Tsoyi, Konstantin; Padera, Robert F.; Sholl, Lynette M.; Goldberg, Hilary J.; et al.
Biobanked, cryopreserved lung cells obtained from human lung tissue are viable and valuable resources for large-scale molecular phenotyping http://bit.ly/31gtpcP